THE IMPORTANCE OF COMPETITION POLICY IMPLEMENTATION IN A SMALL ECONOMY: THE CASE OF THE LITHUANIAN FUEL TRADE MARKET - Baužytė, Inga; Kučaidze, Karina (Ekonomika, 2011)
The paper deals with the importance of competition policy implementation in a small market economy. The Lithuanian fuel trade market has been chosen for the analysis. To ensure that the fuel trade market is working efficiently and is fairly priced is one of the key priorities for the government of Lithuania. Competition policy plays an essential part in the country’s economy. Therefore, in order to understand the characteristics of small market economy and how competition policy is working in such market conditions, it is neassary to realize the complexity of the analysis. The paper offers a brief theoretical overview of the specifications of competition policy in a small market economy, together with a thorough interpretation, empirical research and discussion of the Lithuanian fuel trade market.